Environmental education in practice: adequacy of the disposal of the wastes in an institution of higher education, Porto Alegre, RS , Brazil - Nunes, Daniela Marques; Veiga, Amanda Marques da; Balbueno, Letícia da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The study aimed to develop an adequate environmental awareness for the proper disposal of waste in a IES of Porto Alegre, RS. The survey was conducted through analysis in the dumps the premises of IES and resulted in the observation of waste in large numbers like: Styrofoam cups and plastic and paper. These results were used to formulate a questionnaire that verified the knowledge of academics on the nature of the waste: dry or organic. The results indicated good knowledge about the nature of waste in general, but showed some doubt as to waste: pencil pointed, dirty glasses of yogurt and tissues. From these results we were prepared awareness and environmental awareness strategies that have been developed in the academic community through the use of informative posters and recreational activities